Synthesis, Characterization, and Biological Studies of Organotin(IV) Derivatives with o- or p-hydroxybenzoic Acids - Mohamed A. Abdellah; Sotiris K. Hadjikakou; Nick Hadjiliadis; Maciej Kubicki; Thomas Bakas; Nikolaos Kourkoumelis; Yannis V. Simos; Spyros Karkabounas; Mirela M. Barsan; Ian S. Butler (Bioinorganic Chemistry and Applications)
Organotin(IV) complexes with o- or p-hydroxybenzoic acids (o-H2BZA or p-H2BZA) of formulae [R2Sn(HL)2] (where H2L = o-H2BZA and R = Me- (1), n-Bu- (2)); [R3Sn(HL)] (where H2L = o-H2BZA and R = n-Bu- (3), Ph- (4) or H2L = p-H2BZA and R = n-Bu- (5), Ph- (6)) were synthesized by reacting a methanolic solution of di- and triorganotin(IV) compounds with an aqueous solution of the ligand (o-H2BZA or p-H2BZA) containing equimolar amounts of potassium hydroxide. The complexes were characterized by elemental analysis, FT-IR, Far-IR, TGA-DTA, FT-Raman, Mössbauer spectroscopy, H1, S119n-NMR, UV/Vis spectroscopy, and Mass spectroscopy. The X-ray crystal structures of complexes 1 and 2 have also been determined. Finally, the influence of these complexes 1–6 upon the catalytic peroxidation of linoleic acid to hydroperoxylinoleic acid by the enzyme lipoxygenase (LOX) was kinetically studied and the results showed that triorganotin(IV) complex 6 has the lowest IC50 value. Also complexes 1–6 were studied for their in vitro cytotoxicity against sarcoma cancer cells (mesenchymal tissue) from the Wistar rat, and the results showed that the complexes have high activity against these cell lines with triphenyltin((IV) complex 4 to be the most active one.